PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Tri Hastuti; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to understand and analyze the effect of capital structure and firm size on financial performance on textile and garment companies listed in the Indonesia Stock Exchange in the period 2010-2014. Where variable X1 is capital structure which is indicated by Debt to Equity ratio (DER) and Debt to Assets Ratio (DAR), then for independent variable X2 is Company size which is indicated by Logarithm Natural Total Asset. While for the dependent variable is the financial performance that is indicated by ROA (return on assets), ROI (Return on Investment) and ROE (Return on Equity).The data used in this study is secondary data derived from the financial statements of textile and garment companies listed on the Indonesian stock exchanges in the period 2010-2014. Sampling is done by purposive sampling and that meets the criteria of sample selection. The sample used is 6 textile and garment enterprises. Data analysis by using multiple linear analysis with hypothesis test of t test statistic and statistic test f assisted by SPPS 21 software.The result of the research is partial by using statistical test that is done testing of t test hypothesis, capital structure variable there is significant influence to financial performance on textile and garment sector listed in Indonesia Stock Exchange. The result of partial research by using statistical test yaiti tested t test hypothesis, firm size variable there is significant influence to firm value in textile sector and gamren listed in Indonesia Stock Exchange.Keywords; Capital structure (DER & DAR), size, financial performance (ROA, ROI, ROE